Building Islamic Values In Entrepreneurship In The Perspective Of Al-Quran In Al-Baqarah: 198 And An-Nisa': 29 - Khatimah, Husnul; Nuradi, Nuradi; Haslam, Desy Sapitri; Allifafitri, Aissa; Fitriyani, Fitriyani; Abdel-Raouf, Ahmed Mohamed Abdel-Hadi (ZAD Al-Mufassirin, 2024)
Entrepreneurship is the command of Allah and the Sunnah of His Messenger, which Allah has regulated through the Qur'an. A Muslim entrepreneur not only has a worldly goal in entrepreneurship but also an afterlife goal in it. This study aims to analyze how to build Islamic values in entrepreneurship from the perspective of Al-Quran in Al-Baqarah: 198 and An-Nisa': 29. The research method used is descriptive qualitative method with data collection using literature study. The results of this study indicate that the value of faith and moral values are two things that Muslim entrepreneurs must build in every business they run based on what is contained in Surah Al-Baqarah: 198 and An-Nisa': 29. Thus, Muslim entrepreneurs who have good and correct faith, as well as have morals will affect the quality of the market, which will affect the economy of the community. Building these two Islamic values is not an easy thing, it requires self-awareness from the person of a Muslim in improving the intention when entrepreneurship.